Knowledge, attitude and practices of male condom use among male employees, 50 years and older, at a diamond mining company in southern Namibia - Nakathingo, Phillemon; Lerebo, Wondwossen; Van Wyk, Brian; Nuuyoma, Vistolina (International Journal of Health, 2017)
The HIV and AIDS pandemic has been characterised as the greatest health and development challenge ever to confront humanity, and is one of the great moral curses of our time. The pandemic has hit sub-Saharan Africa, and Namibia is one of the countries which are badly affected. In Namibia, the focus has been on the population aged 15 to 49 years. Hence, this study looks at older men in terms of it being a neglected population.A descriptive, cross-sectional survey utilizing a quantitative research approach was applied. Data were collected through face-to-face interviewing 105 randomly selected male employees aged 50 years and older. Data were captured in MS Excel and then imported into SPSS version 16.0. The level of statistical significance was set at 0.05.This study revealed that respondents’ knowledge about male condoms appeared to be moderate (52.4%). About 92.4% stated that correct and consistent use of male condoms prevents HIV transmission. A larger percentage (85.1%) of respondents disagreed that older men do not need to learn how to use a condom. A high percentage of respondents suggested that HIV-positive individuals should use condoms every time they have sexual intercourse.Men aged 50 years and older are not at risk of contracting HIV due to lack of knowledge of male condom use. Thus, to minimize the likelihood of HIV infection, targeted interventions including peer education programmes were suggested in order to strengthen the practice and attitudes.